SELF CONTROL PADA REMAJA PELAKU SEKS PRA NIKAH - Muhamad Nurdin; Ajeng Ummy Fadhila (Institut Agama Islam Negeri (IAIN) Ponorogo, 2023)
In an Islamic perspective, premarital sex is known as adultery. This means that sexual relations between a man and a woman are not subject to a valid marriage according to Islamic law. But premarital sex among teenagers has become the norm, not something new. The purpose of this research is to identify the factors that cause premarital sex in adolescents, and the forms of behavior change due to self control by adolescents. This study uses a type of qualitative research, collecting data using observation and interview techniques. The data analysis technique used is data reduction, data presentation, drawing conclusions and data validation techniques. In this study, the results obtained were that the factors causing premarital sex behavior experienced by adolescents were caused by curiosity about premarital sex experienced by adolescents and there were family factors and environmental factors. The form of behavior change that occurs due to self control in premarital sex offenders in adolescents uses behavioral control, cognitive control and decision making. And there are forms of behavior change experienced by adolescents after having premarital sex, namely stopping having premarital sex.